Relasion Capability and Product Innovation in Increasing Competitive Advantage the Covid-19 Pandemic (PT. Hanan Boga Rasa) - Wandi Kurniadi (Universitas Kristen Indonesia Toraja, 2022)
At this time, the COVID-19 pandemic is currently sweeping the world, especially our own country, namely Indonesia itself, which has had various impacts, including the economy. The impact of the Corona virus on the economy in Indonesia results in a potential economic growth of 0.4%, which is a bad scenario. With the existence of COVID-19, many were affected, which resulted in many companies terminating their jobs (PHK, Sumarni, and Panday, 2020). Research was conducted to find out whether relational capability and product innovation had an influence on competitive advantage during the COVID-19 period. 19. The method used by researchers using quantitative methods with a sample size of 35 fashion creative industries in the city of Bandung. Researchers used multiple linear regression analysis techniques and hypothesis testing (F and T tests). This study used the SPSS version 25 program. From the results This study shows that there is a significant and positive influence between relational capabilities and competitive advantage, but not between product innovation and competitive advantage during the COVID-19 period.